Impact of dietary protein hydrolysates on cognitive performance: A systematic review of randomized controlled trials involving adults - Micah S. Adams; Ronald P. Mensink; Peter J. Joris (Journal of Functional Foods)
Changes in cerebral blood flow (CBF) - a marker of brain vascular function - may improve cognitive performance, and enhancing CBF through a healthy lifestyle could mitigate cognitive decline. Protein hydrolysates have shown potential to improve brain health. This systematic review analyzed randomized controlled trials on the effects of protein hydrolysates on cognitive performance and CBF in healthy adults and specific target populations. 4747 studies were identified, yielding 13 papers investigating cognitive performance, with four of those also evaluating CBF. Two egg-protein hydrolysates out of five studies on inhibitory control reported cognitive performance improvements. Three out of six studies from various protein sources observed enhancements in visuospatial memory. A link between CBF and cognitive performance was not observed. In conclusion, some studies have indicated that certain protein hydrolysates may benefit cognitive performance, but further research is needed to clarify contradictory findings and to identify beneficial bioactive peptides.